Some functional properties of pigment extracts from red cabbage (Brassica oleracea) and redbeet (Beta vulgaris) - Bruno, E. (2012)
The purpose of the present work was to obtain natural pigments from red cabbage and redbeet. The antioxidant and antimicrobial activities of the fresh pigments were determined. Furthermore, the encapsulation capability and release of the bioactive compounds were analyzed. Pigment extraction was conducted in distilled water with 1% HCl media. The anthocyanin content obtained from cabbage was 8.9 mg /ml and 8.8 mg /ml of betalains from redbeet. The polyphenol content for red cabbage and redbeet were 0.0128 and 0.0123 mg of gallic acid equivalent/g in dry basis, respectively, as determined by Folin-Ciocalteau method. The stability of the extracts to UV light and temperature was assessed; polyphenolic and pigment contents decreased after exposure. Pure extracts from these vegetables showed an antimicrobial effect under ambient conditions, as well as an inhibitory activity against Staphylococcus aureus. However, no antimicrobial effect was detected for the pathogen Aspergillus niger. The extracts were successfully encapsulated in calcium alginate beads; an additional coating of chitosan was applied.